Strategy to Improve al-Quran Reading and Writing Skills in Public Schools - Muharami Aisyah Hanafi; Momod Abdul Somad; Usup Romli; Mustapha Almasi (Journal of Islamic Education Research, 2024)
This research aims to explore strategies for improving Al-Quran Reading and Writing (Baca Tulis al-Quran / BTQ) skills in public schools, with a case study at SMAN 2 Bandung. Studying the Koran is essential for every Muslim that studying the Koran is the most important thing for every Muslim, especially in terms of reading each verse in it which contains certain tajwid laws that must be obeyed when reading it. However, in reality there are quite a few people who still make mistakes in reading and pronouncing the Koran. Reading and Writing the Qur'an is a key skill in Islamic education, focusing on both Arabic mastery and character development, but also contributes to the development of students' character and morals. Data was collected through semi-structured interviews, observations, and document studies, which were then analyzed using the Miles and Huberman model. The results of this research indicate that limited time and minimal support for learning at home are the main challenges in implementing BTQ in public schools. The school applies the "bandungan" method for BTQ learning, where students take turns reading with correction from teachers and classmates, as well as daily Koran assignments at home.